Peningkatan Kemampuan Representasi Matematis Dan Kemandirian Belajar Siswa Menggunakan Pendekatan RME - Indriyani, Yunita Dwi; Sudarman, Satrio Wicaksono; Vahlia, Ira (Jurnal Derivat: Jurnal Matematika dan Pendidikan Matematika, 2020)
The purpose of this research is to improve the mathematical representation ability and learning independence through the Realistic Mathematics Education (RME) approach in students of class XI IPS 1 SMA N 1 Pekalongan. This type of research is a classroom action research study subjects were students of class XI IPS 1 SMA N 1 Pekalongan consisting of 25 students. This can be seen from the students' mathematical representation ability in linear program material by increasing data analysis (N-Gain) from the pre-survey to the first cycle obtained an average pre-test of 59.2 and an average post-test of 64.8 so that gain 0.30 with a percentage of 30% in the low category. Furthermore, the first cycle to the second cycle obtained an average pre-test of 64.8 and an average post-test of 77.4 so that a gain of 0.53 with a percentage of 53% in the medium category. Independence of student learning from pre-survey to the first cycle with a percentage of 54.6% increased to 65.05% with a high category. Furthermore, from cycle, I to cycle II with a percentage of 65.05% increased to 82.9% with a very high category.Keywords:Mathematical Representation, Self-regulated Learning, RME